Integrated chatter avoidance and minimum quantity lubrication conditions for chatter vibration problem in the machining process - Wan Azlan, Wan Mohd Nowalid; A. R., Yusoff (2015)
This paper presents an experimental validation to compare stability lobes diagram between flood and minimal quantity lubrication condition in milling. The cutting condition is the most important factor contributing the machined work piece surface and in determining the acceptable cutting parameters for high productivity in metal cutting industries. Analytical and experimental identifications of the chatter frequencies in millingprocesses are presented.In the case of milling, there are several frequency sets arising from the vibration signals, as opposed to thesingle well-defined chatter frequency of the unstable turning process. Frequency diagrams are constructed analytically and attached to the stability charts of mechanical models of high-speed milling. The corresponding quasiperiodic solutions of the governing time-periodic delay-differential equations are also identified with some milling experiments in the case of highly intermittent cutting.The predicted stability lobes are compared with the micro-milling force signals transformed into the frequency domain. It is observed that the predicted stability limits result in good correlation with the experimentally obtained chatter free conditions.